2008
DOI: 10.1007/s11095-008-9615-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles Enhance the Delivery of the HIV Protease Inhibitor, Atazanavir, by a Human Brain Endothelial Cell Line

Abstract: These data suggest that SLNs could be a promising drug delivery system to enhance brain uptake of atazanavir and potentially other PIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(91 citation statements)
references
References 47 publications
(40 reference statements)
2
89
0
Order By: Relevance
“…40 In vitro studies also showed increased endothelial uptake of solid lipid ATV and transferrin-tagged saquinavir nanoparticles compared with nontagged drugs. 41,42 The current study shows localization of nanoART in endothelial cell vesicles, suggesting that vesicular transport may be involved in nanoART uptake and trafficking in HBMEC. Future investigations will explore the types of vesicles involved and the molecular mechanisms through which endothelial cells uptake nanoART during endothelial-MP communication.…”
Section: Discussionmentioning
confidence: 58%
“…40 In vitro studies also showed increased endothelial uptake of solid lipid ATV and transferrin-tagged saquinavir nanoparticles compared with nontagged drugs. 41,42 The current study shows localization of nanoART in endothelial cell vesicles, suggesting that vesicular transport may be involved in nanoART uptake and trafficking in HBMEC. Future investigations will explore the types of vesicles involved and the molecular mechanisms through which endothelial cells uptake nanoART during endothelial-MP communication.…”
Section: Discussionmentioning
confidence: 58%
“…SLNs may carry both lipophilic and hydrophilic elements. Many substances have been delivered into the brain using SLNs, including camptothecin (RTI International, NC, USA), 165 piperine, 166 docetaxel, 167 small interfering RNA, 168 curcumin, 169 quercetin, 170 idebenone, 171 antiviral agents, 172,173 apomorphine, 174 risperidone, 175 and quinine. 176 Recent reviews have discussed the controversies and benefits of SLNs as carriers of drugs to the brain.…”
Section: Solid Nanoparticlesmentioning
confidence: 99%
“…Although preliminary, the ability of these NLCs to promote intracellular trafficking at a representative cell line of the BBB suggests that these nanocarriers may be a promising system to enhance zidovudine brain uptake. In another study, atazanavir was loaded into stearic acid-based SLNs for enhanced brain delivery by Chattopadhyay et al 92 SLNs produced by a thin-film hydration technique based on a microemulsion possessed negative charges (zeta potential of approximately −18 mV) and a mean particle-size range between 150 and 250 nm. Besides confirming the low toxicity ppotential of SLNs in hCMEC/ D 3 cell line, a human brain microvessel endothelial cell line (HBMEC), up to a concentration corresponding to 200 nM of atazanavir, this group also demonstrated significantly higher drug-permeation ratios through endothelial cell monolayers compared to atazanavir in aqueous solution after 2 hours of incubation.…”
Section: Antiretroviral Drug-loaded Nanoparticles For Cns Deliverymentioning
confidence: 99%